2019
DOI: 10.5409/wjcp.v8.i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of respiratory syncytial virus infection among children hospitalized with acute lower respiratory tract infections in Southern India

Abstract: BACKGROUND Respiratory syncytial virus (RSV) is a leading cause of lower respiratory infections among children. AIM To investigate the proportion of RSV and non-RSV respiratory viral infections among hospitalized children ≤ 5 years. METHODS Hospitalized children aged < 5 years, with a diagnosis of acute lower respiratory infections (ALRI), admitted between August 2011-August 2013, were included. Cases were defined as laboratory-confirmed RSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…19 Although viral infection is the dominant cause of ARIs, the proportion of infections with atypical pathogens is increasing due to the abuse of antibiotics and the development of detection technology. [9][10][11] At present, several studies on the epidemiology and etiology of respiratory pathogens of children in different areas have been reported, 7,16,[20][21][22][23] The result of this study shows that the top three most prevalent pathogens were MP (18.12%, 2816/5597),Flu B (11.65%, 1811/5597) and CP (7.00%, 1088/5597). The total positive detection rate is 36.01% (5597/15443) in Xi'an, which was similar with the previous study in Turkey (33.4 ) and Shandong province in China (35.75 ), 12,18 and signi cantly higher than that reported in Beijing (5.64%), Shenzhen (14.55%), Suzhou (13.6%) and Gansu province in China (29.2%), [13][14][15][16] but lower than that reported in north China (39.3%).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…19 Although viral infection is the dominant cause of ARIs, the proportion of infections with atypical pathogens is increasing due to the abuse of antibiotics and the development of detection technology. [9][10][11] At present, several studies on the epidemiology and etiology of respiratory pathogens of children in different areas have been reported, 7,16,[20][21][22][23] The result of this study shows that the top three most prevalent pathogens were MP (18.12%, 2816/5597),Flu B (11.65%, 1811/5597) and CP (7.00%, 1088/5597). The total positive detection rate is 36.01% (5597/15443) in Xi'an, which was similar with the previous study in Turkey (33.4 ) and Shandong province in China (35.75 ), 12,18 and signi cantly higher than that reported in Beijing (5.64%), Shenzhen (14.55%), Suzhou (13.6%) and Gansu province in China (29.2%), [13][14][15][16] but lower than that reported in north China (39.3%).…”
Section: Discussionmentioning
confidence: 67%
“…3 Respiratory syncytial virus (RSV), in uenza virus A (Flu A), in uenza virus B (Flu B), parain uenza virus (PIV) and adenovirus (ADV) are considered to be the common pathogens of most ARIs. 5 RSV is the leading cause of severe lower respiratory tract infection (LRTIs) in infants and young children, 6,7 while in uenza virus (IFVs) is the main pathogen causing LRTIs in hospitalized adults. 8 In addition, with the increase of antibiotic resistance rate and the development of pathogen detection technology, the research on mycoplasma (MP), chlamydia (CP), legionella (LP) and other atypical pathogens has been gradually deepened, and their role in respiratory tract infections has aroused people's attention.…”
Section: Introductionmentioning
confidence: 99%
“…A smaller peak was also noted during December, January, and February. 23,24,27,47,48 Few Indian studies conducted in North India reported that RSV mainly peaks in winter (November to February) and observed some correlation with low temperature. 44,49 While few studies reported negative co-relation between RSV cases with temperature and rainfall however a, positive correlation (25%-40%) was observed with cool, dry months (December-February).…”
Section: Seasonality Of Rsv In Indiamentioning
confidence: 99%
“…Studies conducted in Indian children from various regions indicated strongest association between RSV and acute lower respiratory infections (ALRI), acute respiratory infection (ARI), upper respiratory infection (URI), lower respiratory tract infection (LRTI) and influenza. 8 , 19 , 23 , 24 , 39 , 40 , 45 , 48 , 49 A study from north India reported 90% and 86% of the RSV–associated hospitalization rates in children with ARI aged <2 years and <5 years, respectively. 36 Outcome of the study conducted by Saxena et al 37 reported simultaneous diagnosis of RSV with influenza in pediatric population which shows that patients with influenza can be considered as high-risk group for RSV infection.…”
Section: Rsv As a Co-infectionmentioning
confidence: 99%
“…Acute lower respiratory infections (ALRIs) are common diseases worldwide, and have a high mortality rate, especially in children, where they account for approximately 30% of child deaths (1)(2)(3). Generally, ALRIs are caused by microbial organisms such as bacteria, viruses, mycoplasma, chlamydia, and legionella.…”
Section: Introductionmentioning
confidence: 99%